Evaluasi Penerapan Strategi Refleksi Terpandu dalam Pembelajaran PJOK untuk Meningkatkan Kesadaran Nilai-Nilai Moral pada Siswa MA NWDI Keruak - Muhsan; Rindawan; Sri Erny Muliyani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to evaluate the effectiveness of the guided reflection strategy in enhancing students’ moral awareness through Physical Education, Sports, and Health (PJOK) learning at MA NWDI Keruak. The research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The sample consisted of 30 students from class XI IPS 1, selected through purposive sampling. The main instrumentwas a 25-item Likert scale questionnaire based on five core moral values: honesty, responsibility, cooperation, sportsmanship, and discipline. The results showed a significant increase in students’ moral awareness scores, from a pretest mean of 84.67 to a posttest mean of 101.93. A paired sample t-test revealed a significance level of p = 0.000 (p < 0.05), and the effect size (Cohen’s d) was 1.56, indicating a large effect. Qualitative data from students’ reflective journals and teacher observations supported the quantitative findings. This study contributes a novel perspective on the application of guided reflection strategies grounded in moral values within Islamic-based madrasah settings, which have been underexplored in physical education literature.